The labyrinth of universality : Wilson Harris's visionary art of fiction - Maes-Jelinek, Hena (Cross/cultures, 2006)
Wilson Harris, many times nominated for the Nobel Prize in Literature, is a British writer of Guyanese origin, one of the most original novelists and critics of the twentieth century, and probably the first to use and interpret the aesthetically fruitful notion of cross-culturalism. Harris's insights into the profound symbiosis between history, culture and artistic expression were initially inspired by his encounters with Amerindians in the Guyanese rainforest interior, where he led many surveying expeditions. These encounters aroused his interest in pre-Columbian peoples, who figure prominent.